The Development and Contributions Of Youth Choirs in Ghana - Esson, E.D.K. (University Of Ghana, 2016)
The primary focus of this study is to examine the development and contributions of youth choirs in Ghana. The research seeks to attempt an in-depth study at the concept of the youth choir as an institution which came to the limelight of choral music industry about three decades ago. The acceptance of this youth choir system due to its economic boom in recent times has gained a maximum popularity as well as provided an avenue for both professional and unprofessional musicians but has not received much scholarly attention. The purpose of the study is to trace the historical events that necessitated the formation of youth choirs and delve into their development and contributions to the socio-economic impart with the specific attention on motivation of the formation, conflict management and the performance practices/styles. The research methodology is primary based on fieldwork which includes discussion, interviews, participant observation during rehearsals sessions and performances, library research, journals and recordings of some of the works performed by the youth choirs. The study discovered that the community youth choirs and all others when properly run will create employment to its members and become an asset to the host community and the nation as a whole in several ways. Youth choir system also provides an avenue to unearth and develop the musical prowess of the youth. It is therefore recommended that every community, institution, government agency and organisation should be encouraged to form a youth choir or sponsor the existing ones since they help to address and solve some of the unemployment issues in the country
Thesis (MPhil.)
Keywords: Youth Choirs; Development; Choral Music; Music; Ghana